PENGARUH SOSIALISASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN - Mella Afrina; M. Royhan Safdan Muzaki Harahap; Try Wahyuni Mawatdah; Dini Vientiyani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the impact of tax socialization on local taxpayers’ compliance with land and building tax (PBB) payments. Although the United Nations is one of the most important sources of Local Owned Revenue (PAD), the low level of community compliance makes it difficult to achieve. One of the main strategies to increase taxpayers’ understanding, awareness, and positive attitude towards tax obligations is to socialize taxes. Quantitative descriptive research was used, with data collection through observation, questionnaires, and documentation studies. The results show that the intensity and quality of tax socialization are positive and significant to taxpayer compliance in paying PBB. The communication media used, individual approach, and involvement of community leaders are proven to affect the effectiveness of socialization. Thus, flexible and sustainable socialization is essential to help optimize local tax revenue. The results showed that there is a positive and significant relationship between the intensity of tax socialization and the increase in compliance with PBB payments. Taxpayers who actively receive information and education about taxes tend to better understand their obligations, pay taxes on time, and behave more obediently to applicable regulations. In contrast, taxpayer awareness and participation are low due to lack of information and communication. The results confirm that flexible and consistent tax socialization is essential to support PBB collection at the local level.